ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS BONGKAR MUAT PETI KEMAS DI PELABUHAN TANJUNG EMAS SEMARANG - Dedy Rusmiyanto; Wempy Trinandya Dessixson (Fakultas Teknik Universitas Maritim AMNI Semarang, 2022)
The flow of containers through Tanjung Emas Port is increasing, this can be seen from the growth of loading and unloading containers from year to year. The condition of the flow of containers is inseparable from the improvement of services at the Container Terminal of Tanjung Emas Port, Semarang through the provision of supporting facilities and infrastructure. With the growth of the container flow which is quite high, the condition of existing facilities, infrastructure and operating systems needs to be reviewed whether the operation is optimal or its performance is still possible to improve, or it is time to add infrastructure and facilities to anticipate future transportation demand. will come. Smooth loading and unloading aims to improve good service in the activities and services of the loading and unloading process of containers according to operational standards. There are several factors that cause the smooth loading and unloading of containers, such as those related to the condition of loading and unloading equipment, the performance of human resources, operations and the environment. In this study, four research variables will be analyzed, namely loading and unloading equipment, human resources, operations and anticipation of natural factors as independent variables and loading and unloading smoothness as the dependent variable. The purpose of this study was to analyze whether the positive influence both individually between the independent variables of loading and unloading equipment, human resources, operations, anticipation of natural factors on the dependent variable, namely the smoothness of loading and unloading. In this study, the object taken is the user of loading and unloading services at Tanjung Emas Port, Semarang. Sources of data include primary data and secondary data. The sample in this study was 100 respondents. The data analysis technique is multiple linear regression technique. Based on the results of research and multiple analysis, the following equations are generated: Y= -0,504 + 0,264.X1 + 0,203.X2 + 0,323.X3 + 0,249.X4 + µ From the results of the multiple regression study, it shows that the most dominant variable affecting the smooth loading and unloading is the operational variable with a regression coefficient of 0.323. . With the Adjusted R 2 test, a result of 0.644 or 64.4% was obtained. Simultaneously, the variables of loading and unloading equipment, human resources, operations and natural conditions factors had an effect of 64.4% on the smooth loading and unloading and 35.6% were influenced by research variables that were not detected in this study.